Implementasi Data Mining Kluster Pada Rumah Tangga Yang Memiliki Akses Hunian Layak Berdasarkan Provinsi - Lisa Novia Ningsi; Poningsih Poningsih; Heru Satria Tambunan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The purpose of this study is to classify household residents who have access to decent housing that can be occupied by the community by province. In this study, the K-Means Clustering Algorithm is used, which is a method that partitions data into one or more clusters that have the same characteristics as each other based on the results obtained. Sources of data in this study were obtained from the website of the Central Statistics Agency (BPS) with the url address https://www.bps.go.id/. The data used in this study is data on the percentage of households that have access to decent and affordable housing according to provinces in 2015-2018, which consists of 34 provinces. The variable used is the average percentage of households that have access to decent and affordable housing by province. The data will be processed by dividing the clusters into 2 parts, namely clusters with low-level status and clusters with high-level status. It is hoped that the results of this study can provide input for the leadership regarding the policy of budget allocation in the APBN to be more effective in contributing to overcoming the problem of decent and affordable housing to live in.